Severe Psychopathology and Substance Use Disorder Modify the Association Between Housing Trajectories and Food Security Among Homeless Adults - Lachaud, James; Mejia-Lancheros, Cilia; Liu, Michael; Wang, Ri; Nisenbaum, Rosane; Stergiopoulos, Vicky; Hwang, Stephen W.; O'Campo, Patricia (Frontiers in Nutrition, 2021)
Purpose: We examined the housing trajectories of homeless people with mental illness over a follow-up period of 6 years, and the association of these trajectories with food security. We then examined the modifying role of psychopathology and alcohol and substance use disorders in this association. Materials and Methods: We followed 487 homeless adults with mental illness at the Toronto site of the At Home/Chez-Soi project –a randomized trial of Housing First. Food security data were collected 7 times during the follow-up period. Psychopathology (Colorado Symptom Index score) and alcohol and substance use disorders were assessed at baseline. Housing trajectories were identified using group-based trajectory modelling. Logistic regression was used to estimate the association between housing trajectory groups and food security. Results: Three housing trajectory groups were identified: a rapid move to consistent stable housing (34.7%), slow and inconsistent housing (52.1%), and never moved to stable housing (13.2%). Individuals included in the rapid move to consistent housing trajectory group had higher odds of remaining food secure compared to those in the never moved to stable housing trajectory group over the follow-up period [AOR 2.9, 95% CI: 1.3-6.6, P-value: 0.009]. However, when interactions were considered, this association was significant among those with moderate psychopathology but not severe psychopathology. Individuals with substance use disorder and in the group never move to stable house group had the lowest food security status. Discussion: Severe psychopathology and substance use disorders modified the association between housing trajectories and food security. International Standard Randomized Control Trial Number Register (ISRCTN42520374).